Effect of matrix suction on the shear strength characteristics of reinforced granite residual soil - Deng, Xiangwen; Zhu, Zhengyu; Lin, Xi yang; Yang, Xue qiang (Frontiers in Materials, 2023)
The soil in geogrid-reinforced structures is typically unsaturated, with the shear strength provided by both the matrix suction and the reinforced body. Traditional structural designs for saturated soils only consider the shear strength provided by the reinforced body, neglecting the part provided by matrix suction. As a result, the design for reinforced structures is biased towards conservatism.The study examined the matrix suction-provided shear strength in reinforced soils through strain-controlled triaxial and soil-water characteristic curve(SWCC) pressure plate instrumentation. Verified the feasibility of the Schrefler and Khalili unsaturated soil shear strength formula for predicting shear strength based on matrix suction forces.The study revealed that the cohesion of saturated reinforced soil exhibits a significant decrease in contrast to unsaturated reinforced soil, with matrix suction serving as a crucial consideration for reinforced structure design.The experimental results confirm the suitability of applying the quasi-cohesion increment theory to reinforced clays.The Khalili formula can be utilized to predict the quasi cohesion of unsaturated reinforced soils with greater accuracy under diverse dry density conditions. The results obtained using post-shear moisture content were closer to the measured values than those using initial moisture content.